Disease knowledge and health literacy in parents of children with sickle cell disease - Bonaventure G. Ikediashi; Cristina Ehrmann; Selma Gomez; Gisela Michel (eJHaem, 2023)
Abstract We aimed to (1) describe sickle cell disease (SCD) knowledge and health literacy levels in parents of children with SCD, (2) examine associations with socio‐demographic factors and (3) analyse the association with hospital admissions and frequency of occurrence of painful episodes. Parents who presented with their child at routine hospital consultation at the National Sickle Cell Disease Centre in Benin were administered a questionnaire assessing SCD knowledge, health literacy (newest vital sign [NVS]) and socio‐demographic and clinical characteristics. In total, 117 parents participated (108, 92.3% females). The predominant SCD genotype was HbSS (79.5%). The average SCD knowledge score was 13.6 (standard deviation [SD] = 2.0). Only 34 (29.1%) participants correctly answered ≥70% of the questions, indicating good knowledge. Health literacy was relatively low (mean NVS score = 3.3; SD = 1.1). SCD knowledge was higher in parents with older children (p = 0.001) and higher education levels (primary, p = 0.010; tertiary, p = 0.036 compared to participants with no formal education). Hospital admissions were more frequent when parents had lower SCD knowledge (p = 0.034) and in parents with younger children (p = 0.039). No associations were found between health literacy and hospital admissions (p = 0.940) and frequency of occurrence of painful episodes (p = 0.224). Continuous disease‐specific education for parents of children with SCD may help them better identify and prevent the occurrence of symptoms and decrease the number of hospital admissions.